WHY DO PHILOSOPHERS AND EDUCATORS KEEP COMING BACK TO HANNAH ARENDT? - Gordon, Mordechai (Cadernos Arendt, 2023)
It has been over twenty years since my collection of essays Hannah Arendt and Education: Renewing our Common World was first published (2001, Westview Press).2 The novelty of this book was in its being the first to make an explicit connection between Arendt’s political concepts and the field of education. Before the publication of Hannah Arendt and Education: Renewing our Common World very few articles and no books had been written that explored the implications of her insights for educational theory and practice. In part for that reason, my original prediction was that the 2001 collection of essays on Arendt and education would be a niche book, one that would appeal to a relatively small number of Arendtian scholars. Fortunately, this prediction proved to be wrong and Hannah Arendt and Education: Renewing our Common World reached a much broader audience than I had anticipated. In fact, this book is still in print, having sold thousands of copies, translated into several languages, and continues to receive favorable reviews.